50th Edition of WILGA Symposium on Photonics Applications - Romaniuk, Ryszard S. (Photonics Letters of Poland, 2022)
The Jubilee 50th edition of WILGA Symposium on Photonics Applications crowns 25 years of diligent service by this exceptional series of scientific and technical meetings to the local and international photonics research, academic, industrial, business and societal communities. The paper reviews concisely, and only generally without details, some of the chosen topical tracks related to photonics present during the previous meetings and in particular during WILGA 2022 sessions. The paper summarizes shortly the achievements of WILGA Photonics Applications meetings of young researchers, during the quarter of a century, and gives a general sense of the unique nature of these meetings. Wider description of WILGA achievements are available in around 30 Proc. SPIE volumes published continuously under the common title Photonics Applications in Astronomy, Communications, Industry, and High-Energy Physics Experiments in the years 2002-2022. Full Text: PDF References WILGA Symposium on Photonics Applications DirectLink Sympozjum WILGA CrossRef R.S.Romaniuk, "Photonics Applications, WILGA Symposium 1998-2022", Elektronika 63(4) 30, 2022 CrossRef R.R. Romaniuk, "More light in Polish optical fibers", Proc. SPIE 5125 (2002) CrossRef WILGA Photonics Applications 2021, Proc. SPIE 12040 CrossRef WILGA Photonics Applications 2022, Proc. SPIE, in press CrossRef United Nations International Year of Glass 2022 DirectLink .